The Birth of German Biotechnology Industry - Did Venture Capital run the show? - Oliver Heneric; Dirk Engel; Claire Champenois (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2004)
We answer the questions, how many firms acting in the modern German biotechnology industry are funded by venture capital companies (VCC) as well as equity funded by corporate investors. The theory suggests a high relevance of VCC as venturing partner of high-tech projects. In addition we argue that corporate investors are a venturing partner of firms with high-risk projects to a lower extent. Incumbents,however, are confronted with some opportunities in the low-risk area of the biotechnology industry to secure an optimal supply for the current product pipeline.Our empirical results emphasize a crucial importance of venture capital as financial resource for high-risk projects: whereas 42 percent of all healthcare developer in the early stage are venture-backed firms, only a small share of low-risk projects received venture capital. The results for corporate investors are reversible.Fewer high-tech projects and more low-risk projects compared to VCC are equity financed by corporate investors. The econometric analysis suggests that the observed pattern is mainly driven by the level of project risk and hence, supports all our hypotheses.
Keywords: C25; L21; G32; 330; Biotechnology; Start-ups; Venture Capital; Discrete Choice; Biotechnische Industrie; Unternehmensgründung; Risikokapital; Schätzung; Deutschland